2016
DOI: 10.3346/jkms.2016.31.11.1717
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Progression and Cytokine Profiles of Middle East Respiratory Syndrome Coronavirus Infection

Abstract: Clinical progression over time and cytokine profiles have not been well defined in patients with Middle East respiratory syndrome coronavirus (MERS-CoV) infection. We included 17 patients with laboratory-confirmed MERS-CoV during the 2015 outbreak in Korea. Clinical and laboratory parameters were collected prospectively. Serum cytokine and chemokine levels in serial serum samples were measured using enzyme-linked immunosorbent assay. All patients presented with fever. The median time to defervescence was 18 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
186
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(203 citation statements)
references
References 23 publications
10
186
0
7
Order By: Relevance
“…The finding of the current study that the severity of illness is associated with a prolonged time interval between onset and diagnosis is consistent with the study by Kim et al, (2016b). The estimated time interval between onset and diagnosis in patients with severe illness was 6.19 days, while it was 5.06 days in patients with a stable condition.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The finding of the current study that the severity of illness is associated with a prolonged time interval between onset and diagnosis is consistent with the study by Kim et al, (2016b). The estimated time interval between onset and diagnosis in patients with severe illness was 6.19 days, while it was 5.06 days in patients with a stable condition.…”
Section: Discussionsupporting
confidence: 92%
“…The average time interval to a confirmed diagnosis after symptom onset was 5.6 days (median 4 days). Kim et al reported a similar median estimate (5 days) in a sample of MERS patients in the Republic of Korea (Kim et al, 2016b).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Taken together, the high expression of inflammatory cytokines/ chemokines IL-1 α and IL-1β, IL-8 (CXCL8), IL-18, CXCR3, SOCS5, and CCR2 in the lower respiratory tracts of MERS-CoV infected patients confirmed the lung immunopathology [46,[77][78][79][80]. Therefore, the high expression of inflammatory cytokines and downregulation of the Th1 and Th2 immune responses in the lower respiratory tracts of MERS-CoV infected patients may contribute to a more severe infection, higher case fatality, lung inflammation, and immunopathology.…”
Section: Resultsmentioning
confidence: 63%